Pengaruh Intelectual Capital Disclosure, Profitabilitas dan Leverage terhadap Firm Value: Studi pada Perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Suandra, Sandrina Putri Fajriyanti (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This research aims to analyze the influence of Intellectual Capital Disclosure (ICD), profitability, and leverage on company value in companies included in the LQ45 index on the Indonesia Stock Exchange for the 2020–2024 period. The research background is based on the importance of disclosing intellectual capital, financial performance and capital structure in increasing company value, as well as the inconsistent results of previous research. The research method uses a quantitative approach with an explanatory design, purposive sampling technique, and data analysis using multiple linear regression. The research sample consisted of 31 companies with a total of 155 observations. The research results show that ICD and profitability have a significant positive effect on company value, while leverage has a significant negative effect. Simultaneously, these three variables have a significant effect on company value with an explanatory power of 54.8%. These findings imply the importance of transparent intellectual capital disclosure, increasing profitability, and careful leverage management as strategies to increase company value and investment attractiveness in the capital market.